Europe on the road to Doha: Towards a new global trade round - J. Peter Neary (University College Dublin, Department of Economics, 2003)
This paper reviews progress to date towards a new trade agreement under the Doha Development Agenda. Some of the key issues in contention are examined, including barriers to trade in agriculture and manufacturing, intellectual property rights, and competition policy. A potential sticking point is whether the US will accept a quasi-judicial role for the WTO and constraints on the use of anti-dumping policy. European governments need to decide how badly they want to complete a new trade agreement, and should start preparing their constituents for compromise if an agreement is to be reached.
hdl:10197/1292
Keywords: 330; Internationale Handelspolitik; Außenhandelsbeschränkung; Immaterialgüterrechte; Wettbewerbspolitik; EU-Staaten; Welt